8q24 amplification is associated with Myc expression and prostate cancer progression and is an independent predictor of recurrence after radical prostatectomy - Fromont, Gaelle; Godet, Julie; Peyret, Antoine; Irani, Jacques; Celhay, Olivier; Rozet, François; Cathelineau, Xavier; Cussenot, Olivier (Human pathology, 2013)
Genomic alterations affecting the 8q24 region are frequent in prostate cancer. Together with the oncogene MYC, other genes located in the surrounding of the amplified region could also be candidate targets. Tissue microarrays were constructed with prostate cancer tissues from (1) a case-control population of patients treated by radical prostatectomy (n = 242; 121 cases with biochemical relapse matched with 121 cancers with identical clinicopathologic features but without relapse), (2) castration-resistant disease (n = 55), and (3) metastatic cancers (n = 28). Fluorescence in situ hybridization and immunohistochemistry were used on tissue microarrays and slides to analyze, respectively, the amplification status of 8q24 and protein expression of genes located at 8q24. Amplification at the MYC locus was observed in 29% of cases and was closely associated with both disease progression (from 15% in pT2 tumors to 53% in metastasis; P = .001), and Gleason score (from <3% in Gleason 6 tumors to 66% in Gleason 8 and more tumors; P < .0001). The expression of genes located at 8q24 did not correlated with the amplification status, except for the Myc protein (P = .002). MYC amplification status but not Myc protein expression was significantly predictive of biochemical recurrence after prostatectomy, together with the proliferation marker Ki-67 and independently from known prognostic factors, including TNM stage and Gleason score. The MYC amplification status could constitute a useful prognostic tool for patients treated by radical prostatectomy, particularly for those with d'Amico intermediate risk, whose clinical behavior is currently difficult to predict.